A review of historical investigations into light and the understanding of colors (Research, Society and Development, 2022)
In this work, knowing that the little importance of scientific dissemination can lead to the weakening of critical thinking in individuals in obtaining adequate knowledge. We present a methodology of three traditional classes with a logical sequence that can be applied to elementary and high school students and the lay population. For the best functioning of the class proposal, to contemplate the content of the study of light, we recommend that the classes be applied in conjunction with teachers of history, philosophy and biology. The present work was a historical research with a systematic sequence in which we describe the development of some centuries of studies on the nature of light. In the course of the work, we analyzed graphs on the electromagnetic spectrum, temperature of the stars, the composition of the Sun and the color of the Sun. Then, we start from the emission of light until it arrives on Earth, with light scattering in the atmosphere. It presents the functioning of the human eye to capture light, an explanation about the colors of objects and why we see, bringing the biological reasons involved. Finally, we leave it to the education professional to use the information presented throughout the text as a basis to help him share the theme of light and make an interdisciplinarity in the way that is convenient.